Sodium Chloride Crystallization by Electric Discharge in Brine - Jairo Breno Francisco de Oliveira Barauna; Camila Senna Pereira; Ingrid Azevedo Gonçalves; Jussier de Oliveira Vitoriano; Clodomiro Alves Junior (Materials Research, 2017)
Electrical discharges in liquids are currently used to synthesize nanoparticles. The plasma-liquid interaction is complex, where parameters such as electric field, ion charges and other species present are important. In order to understand the mechanism of crystallization, mother liquor (saturated solution of NaCl, MgCl2 and KCl) was used to study the effectiveness and selectivity of the crystallization caused by the application of plasma. Discharge was applied with the solution at room temperature or during cooling. X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and chemical analysis was used to evaluate the structure and composition effects on crystal structure and composition. It was observed that the discharge induces selectively crystallization, and when compared to crystals obtained conventionally by cooling, were smaller and more uniform. We therefore confirm that plasma in liquid can also be used to selectively crystallize materials in atmospheric pressure, where the sizes of the crystals must be dependent on the parameters used.